Addenda and corrigenda to the "Annotated catalogue of the Laniatores of the New World (Arachnida, Opiliones)" - Kury, Adriano B.; Alonso-Zarazaga, Miguel A. (Zootaxa, 2011)
Amendments are made to inconsistencies, mistakes and omissions in the catalogue of American Laniatores by Kury (2003). Discrepancies between dates given in Kury (2003) and Neave’s Nomenclator and the Zoological Record are discussed. Accurate issue dates for relevant publications are used to define priorities. Etymologies are surveyed for generic names, establishing their grammatical gender, so specific names are inflected according to the provisions of the Code. Unavailable generic names are: Messa Sørensen, 1932, Zarax Sørensen, 1932, Prasia Sørensen, 1932, Angistrisoma Roewer, 1932, Angistrisoma Mello-Leitão, 1935, Bunoweyhia Mello-Leitão, 1935, Batomites Mello-Leitão, 1931, Euminua Sørensen, 1932, Minua Sørensen, 1932, Ilhastygnus Roewer, 1943, Fonteboatus Roewer, 1931, Malea Sørensen, 1932, Chersobleptes Sørensen, 1932 and Jimeneziella Avram, 1970. Hernandria Banks, 1909 is unavailable and must be placed as an “incorrect subsequent spelling” of Hernandaria Sørensen, 1884. The valid genus name is Parahernandria Goodnight & Goodnight, 1947 (stat. res.). Zaraxolia Strand, 1942 (stat. res.) is revalidated from the synonymy of Neocynorta Roewer, 1915 with Zarax devians Sørensen, 1932 as type species. Friburgoia Mello-Leitão, 1932 [December] is deemed a junior subjective synonym of Schenkelibunus Strand, 1932 [September] (stat. res.) (inverted precedence between synonyms). Liops Mello-Leitão, 1940 (non Fieber, 1870, nec Gidley, 1906) is a junior homonym and is replaced by its first available synonym, Corcovadesia Soares & Soares, 1954 (stat. res.). The following unavailable generic names are formally described as new: (1) Jimeneziella Kury & Alonso-Zarazaga, gen. nov. (type species: Jimeneziella decui Avram, 1973); (2) Euminua Kury & Alonso-Zarazaga, gen. nov. (type species: Euminua brevitarsa Sørensen, 1932). The following homonym generic names are replaced: (1) Cranellus Roewer 1932, with Narcellus Kury & Alonso-Zarazaga, nom. nov., (2) Metapachylus Pickard-Cambridge, 1905, with Pyropharynx Kury & Alonso-Zarazaga, nom. nov.; (3) Ovalia González-Sponga, 1987, with Oo Kury & Alonso-Zarazaga, nom. nov.; (4) Tiara González-Sponga, 1987 with Mitraia Kury & Alonso-Zarazaga, nom. nov.; (5) Limonia González-Sponga, 1998, with Manuelangelia Kury & Alonso-Zarazaga, nom. nov. Gonyleptes melloleitaoi Kury & Alonso-Zarazaga, nom. nov. is a replacement name for Gonyleptes curvicornis Mello-Leitão, 1932. Discocyrtus confusus Kury, 2003 is unavailable, so this species is here re-described as Discocyrtus confusus Kury n. sp. New combinations are: Parahernandria spinosa (Banks, 1909) (from Hernandaria), Schenkelibunus impar (Mello-Leitão, 1932) (from Friburgoia), Schenkelibunus perditus (Mello-Leitão, 1927) (from Friburgoia), Narcellus balthazar (Roewer, 1932) (from Cranellus), Narcellus montgomeryi (Goodnight & Goodnight, 1947) (from Cranellus), Pyropharynx gracilis (Pickard-Cambridge, 1905) (from Metapachylus), Oo spinosum (GonzálezSponga, 1999) (from Ovalia), Mitraia unispina (González-Sponga, 1987) (from Tiara), Manuelangelia tuberosa (González-Sponga, 1998) (from Limonia), Zaraxolia devians (Sørensen, 1932) (from Zarax), Corcovadesia hexabunus (Mello-Leitão, 1940) (from Liops) and Corcovadesia venefica (H. Soares, 1966) (from Liops). The following genera of Pachylinae, which appeared in conflicting subfamilies in Kury 2003, are formally transferred to the Ampycinae: Ampycella Roewer, 1929, Glysterus Roewer, 1931, Hernandarioides Pickard-Cambridge, 1905, Parahernandria Goodnight & Goodnight, 1947 and Hutamaia Soares & Soares, 1977. A list of taxa described in 2003 is interpolated. A complementary list of the 2004–2009 systematic literature on the subject is given.